TECHNO-ECONOMIC ANALYSIS OF WASTE-OIL HVO WITH CCUS/EOR AND CARBON TRADING FOR INDONESIA’S DECARBONIZATION - Riadhi, Rizky Maulana; Oktavian, Rama (Jurnal Geosaintek, 2026)
Abstract. Indonesia’s transport and industrial sectors remain deeply dependent on diesel fuel, which accounts for 30% of transport-related CO₂ emissions. Conventional biodiesel blending has delivered limited mitigation due to technical constraints and feedstock competition, underscoring the need for advanced alternatives. This study evaluates the techno-economic feasibility of producing Hydrotreated Vegetable Oil (HVO) from used cooking oil (UCO), combined with process optimization, carbon capture utilization and storage (CCUS) through enhanced oil recovery (EOR), and integration into carbon trading mechanisms. Using Aspen Hysys simulation, a base case retrofit yielded 21.307 kg/h of HVO with an emission intensity of 0,068 kg CO₂ per litre. Incorporation of a refrigeration cycle reduced utility demand by 36%, eliminated direct heater emissions, and lowered carbon intensity to 0,0042 kg CO₂ per litre, representing a 92,5% reduction. Liquefied CO₂ captured from the process provided additional revenue of about US 38,8 million annually when sold for EOR. Coupled with carbon credit monetization under Indonesia’s Carbon Economic Value framework, the effective HVO price declined from IDR 25.000 to about IDR 19,500 per litre, while return on investment increased by up to 42% and internal rate of return improved by nearly 25%. Integrating EOR and carbon trading not only strengthens project returns but also directly addresses Indonesia’s reliance on diesel, which contributes 30% of transport-related CO₂ emissions. By lowering the effective cost of HVO, these mechanisms enable 50% HVO–Pertamina Dex blends to approach Pertamina Dex prices while delivering higher cetane numbers, offering a technically superior and economically viable pathway beyond the limits of conventional biodiesel blending.